2011
DOI: 10.1371/journal.pone.0021397
|View full text |Cite
|
Sign up to set email alerts
|

Wnt/β-Catenin Signaling Induces the Aging of Mesenchymal Stem Cells through the DNA Damage Response and the p53/p21 Pathway

Abstract: Recent studies have demonstrated the importance of cellular extrinsic factors in the aging of adult stem cells. However, the effects of an aged cell–extrinsic environment on mesenchymal stem cell (MSC) aging and the factors involved remain unclear. In the current study, we examine the effects of old rat serum (ORS) on the aging of MSCs, and explore the effects and mechanisms of Wnt/β-catenin signaling on MSC aging induced by ORS treatment. Senescence-associated changes in the cells are examined with SA-β-galac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
138
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 175 publications
(145 citation statements)
references
References 42 publications
6
138
0
1
Order By: Relevance
“…Our study builds on previous work implicating β-catenin in the regulation of genome stability (Aoki et al, 2007;Dose et al, 2014) and in the DNA damage response (Chandra et al, 2015;Priolli et al, 2013;Tavana et al, 2013;Xu et al, 2008;Zhang et al, 2011). Indeed, our data align well with these previous reports.…”
Section: Discussionsupporting
confidence: 90%
“…Our study builds on previous work implicating β-catenin in the regulation of genome stability (Aoki et al, 2007;Dose et al, 2014) and in the DNA damage response (Chandra et al, 2015;Priolli et al, 2013;Tavana et al, 2013;Xu et al, 2008;Zhang et al, 2011). Indeed, our data align well with these previous reports.…”
Section: Discussionsupporting
confidence: 90%
“…Recently, it has also been shown that Wnt1 might induce senescence in mesenchymal cells. 24 Interestingly, atorvastatin at 10 À 5 M induced the expression of Wnt1 and its downstream effector WISP-2 ( Figure 6), a repressor of the TGF-b pathway. 26 We also investigated senescence in vivo using p21 and b-galactosidase staining in rats treated for 1 week with atorvastatin 3 and 5 weeks after BDL (Figures 7 and 8).…”
Section: Discussionmentioning
confidence: 96%
“…24 We investigated this as a third line of evidence for increased senescence of MFB upon incubation with atorvastatin. Indeed at a concentration of 10 À 4 M, Wnt1 expression was undetectable, but mRNA levels of Wnt1 were highly increased at concentrations of 10 À 5 and 10 À 6 M (Figure 6d).…”
Section: Atorvastatin Incubation Induced Senescence In Mfbmentioning
confidence: 99%
See 1 more Smart Citation
“…After sterilization under UV light in a 24‐well plate, the patches were washed with PBS and then immersed in DMEM for 2 hrs before use. MSCs were isolated from bone marrow of male SD rats 18. All animals were obtained from the Medical Institute Animal Center of Fudan University.…”
Section: Methodsmentioning
confidence: 99%